the PHENOTYPIC DIVERSITY ASSESSMENT OF MOROCCAN LOQUAT (ERIOBOTRYA JAPONICA LINDIL.) USING MULTIPLE CORRESPONDENCE ANALYSIS - Ghizlane, KABIRI; LACHKHAM, Fatima Zahra; KODAD, Oussama; HERNANDEZ, Francisca; ENNAHLI, Said; HANINE, Hafida (Journal of Agricultural Sciences (Belgrade), 2023)
The loquat fruit has a very important commercial value due to its benefits on human health. However, there is very limited scientific research on this species in Morocco. I this regard, a set of 35 genotypes were collected from of zegzel valley of Berkane. The phenotypic variability was evaluated using nine traits related to fruit and leaf. The results revealed a coefficient of variation varying from 13.02 to 42.21 %, which means a large phenotypic variation in Moroccan loquat, especially the characteristics associated to the fruit shape. Regarding the multiple correspondence analysis, the first two axes explained 62.57% of the total variance. The major traits allowing to the distinction between genotypes were the characteristics related to fruit size. Therefore, the genotypes called, Mekerkba in the region of Zegzel, is not a single variety but they are genotypes having a round fruits shape. In addition, the 35 accessions studied were divided into three main groups independently of their origin geographic. Indeed, the results indicated that the geographical proximity has not an important role in the genotypes structure of accessions, meaning a weak adaptation of genotypes to the environment. The findings generated by this study could be used in conventional breeding and in situ conservation programs of Moroccan loquat
Keywords: Eriobotrya japonica, phenotypic variability; quantitatives traits; coefficient of variation; multiple correspondence analysis